Long-Term Impairment From Irritant-Induced Occupational Asthma - Lantto, Jussi; Suojalehto, Hille; Vasankari, Tuula; Karvala, Kirsi; Lindström, Irmeli (Lippincott, Williams & Wilkins, 2025)
Objective: The aim of the study is to assess the long-term physical condition, health-related quality of life, employment, and work ability of irritant-induced asthma (IIA) patients.
Methods: Forty-three IIA patients completed a follow-up questionnaire a median of eight (interquartile range 4-11) years after asthma diagnosis. We compared their results with those of 43 low-molecular-weight (LMW) sensitizer-induced occupational asthma (OA) patients and those of 206 adult-onset asthmatics in the general population.
Results: Of the IIA patients, 40% reported depressive symptoms. Of the <65-year-olds, 56% were employed, of whom 39% assessed their work ability as limited. IIA patients had more difficulty climbing several flights of stairs than LMW-induced OA patients (70% vs 47%, OR = 4.83 95% CI: 1.51-15.47). Most of the IIA patients' outcomes were inferior to those of the adult-onset asthmatics in the general population.
Conclusions: IIA prognosis appeared poor but resembled that of LMW-induced OA.